PRACTICING GREEN HRM TO ACHIEVE ENVIRONMENTAL SUSTAINABILITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The essential point of the ponder is to investigate and discover the affiliation between organizational natural maintainability and utilizing green HRM (green compensation, green hiring, green involvement, and green training), as well as to ascertain the role that an employee's green behavior may play in making the entire work settings green. Environmental responsibility is a crucial area of study. Manufacturing companies worldwide are calling for the advancement of their green center projects due to the growing concern for the environment and its effects on global warming and climate change. In a similar vein, it was emphasized that to gain a competitive edge, there is a constant need for the production and exchange of innovative green ideas while taking into account diverse environmental groups throughout the world. The researchers adopted a qualitative methodology. The study examines the relationship between variables, finding that environmental sustainability and staff green behavior correlate with green HRM.